Evaluasi Pelayanan Kependudukan Dalam Peningkatan Pelayanan Publik Dari Peran Kepala Seksi Pelayanan Di Kantor Desa Medalem, Kabupaten Blora - Karyati, Dwi; Wirawan, Arif Wahyu (Universitas Negeri Semarang, 2025)
This study aims to evaluate the quality of population services provided by the Head of Service in Medalem Village, Kradenan District, Blora Regency. The research method used is descriptive qualitative with a case study approach. Data collection techniques are carried out through interviews with village officials and the community, direct observation, and analysis of administrative documents. The results of the study indicate that population services in Medalem Village have been quite good in terms of administrative procedures and service times. Employees are friendly to residents, residents feel comfortable when taking care of documents. Things that need to be improved in services in Medalem Village are the application of technology such as online-based service systems and openness of information, especially related to service procedures on the notice board.